Aktivitas Antibakteri Senyawa Sekunder dari Penicillium citrinum DSP 16 yang Diisolasi dari Daun Sesuvium portulacastrum di Pulau Lombok - Safwan Safwan; Baiq Desti Isnanda Maolia; Yuli Fitriana; Abdul Rahman Wahid; Widayatul Khairi (Universitas Hamzanwadi, 2026)
The discovery of novel antibacterial compounds from natural sources remains a significant focus in drug development, especially with the growing issue of bacterial resistance to existing antibiotics. One promising approach involves the exploration of endophytic fungi that form symbiotic relationships with plants. This study aimed to isolate and cultivate Penicillium citrinum DSP 16, obtain a crude ethyl acetate extract from solid-state fermentation, profile the extract by thin-layer chromatography (TLC), and assess antibacterial activity against Escherichia coli and Staphylococcus aureus using the disk diffusion method. The crude extract produced inhibition zones of 15.2 mm against E. coli and 17.0 mm against S. aureus, indicating strong activity. TLC revealed multiple spots under UV 254/366 nm, suggesting a mixture of secondary metabolites. These findings support P. citrinum DSP 16 as a promising natural source of antibacterial agents and highlight the value of exploring endophytic fungi from halophytic coastal plants.